It's not depersonalization, It's emotional labor: Examining surface acting and use-of-force with evidence from the US. (June 2020) - Mastracci, Sharon H.; Adams, Ian T.
Abstract: Using data from one urban police department in the United States, this study gauges the effects of individual officer characteristics on use-of-force. Consistent with prior research, we find Emotional Exhaustion to be a negative correlate to use-of-force: Emotionally-exhausted officers avoid engaging with others. However, unlike previous research, we examine administrative data on actual use-of-force and include emotional labor into the model to reveal Surface Acting as a positive and significant correlate to use-of-force, while depersonalization has no effect. Other positive and statistically-significant correlates to use-of-force include number of primary calls and perceived need for use-of-force. In contrast, sex, years of experience, and prior military experience do not explain variations in use-of-force, nor does perceived organizational support or serving in a line officer capacity. We conclude with suggestions for further research, including examining use-of-force as a workplace stressor and the potential for emotional suppression to alter officer interpretations of suspect behavior.